2019
DOI: 10.3390/medicina55070338
|View full text |Cite
|
Sign up to set email alerts
|

Association between Circle of Willis Configuration and Rupture of Cerebral Aneurysms

Abstract: Background and Objectives: Intracranial hemorrhage caused by the rupture of brain aneurysms occurs in almost 10 per 100,000 people whereas the incidence of such aneurysms is significantly higher, accounting for 4–9%.Linking certain factors to cerebral aneurysm rupture could help in explaining the significantly lower incidence of their rupture compared to their presence. The aim of this study is to determine the association between the corresponding circle of Willis configurations and rupture of cerebral aneury… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
11
0
5
Order By: Relevance
“…Circle variation has implications for clinical practice. It is associated with an increased risk of ischaemic stroke (Oumer et al, 2021; van Seeters et al, 2015), aneurysm rupture (Lazzaro et al, 2012; Stojanović et al, 2019), white matter disease (Chuang et al, 2011; Ryan et al, 2015) and migraine (Henry et al, 2015). It is also associated with an increased risk of vasospasm post‐subarachnoid haemorrhage (Jacquens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circle variation has implications for clinical practice. It is associated with an increased risk of ischaemic stroke (Oumer et al, 2021; van Seeters et al, 2015), aneurysm rupture (Lazzaro et al, 2012; Stojanović et al, 2019), white matter disease (Chuang et al, 2011; Ryan et al, 2015) and migraine (Henry et al, 2015). It is also associated with an increased risk of vasospasm post‐subarachnoid haemorrhage (Jacquens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…F I G U R E 6 Group three of the classification system containing circles with hypoplastic and absent segments only CoW variation is associated with an increase in aneurysm rupture (Lazzaro et al, 2012;Stojanović et al, 2019). It is suggested that future studies investigate the association between variation type, as described in the classification system, and the risk of aneurysm rupture.…”
Section: Educational Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The arrangement of this arterial circle is subject of multiple variations, such as aplasia, hypoplasia and duplication of its main components (Okahara et al, 2002;Kapoor et al, 2008;Dimmick & Faulder, 2009). In this sense, variations of this classic pattern are frequent, the presence of hypoplasia and /or aplasia would be linked to the development of ischemic encephalic disorders (Hoksbergen et al, 2003;Karatas et al, 2016;Zhou et al, 2018;Stojanovic et al, 2019;Jones et al). Following this line, the hypoplasia of these vessels are considered as the existence of less than 1 mm external caliber, for both, the A1 and P1 arterial segments and for the ACoA and PCoA (Eftekhar et al, 2006;Karatas et al;El Falougy et al, 2018;Jones et al).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios han mostrado variaciones anatómicas de dicha configuración tanto en material cadavérico como en imágenes diagnósticas, que han descrito la presencia de variantes anatómicas entre un 38 % y un 60 % (5)(6)(7)(8). También se ha descrito la relación de dichas variantes con diversas patologías como aneurismas, rupturas aneurismáticas, infartos cerebrales por procedimientos endovasculares (9)(10)(11) o, incluso, el impacto en la capacidad de compensación en los ataques cerebrovasculares isquémicos (12). Por otra parte, la presencia de variantes anatómicas es importante en la realización de procedimientos como el test de Wada, entre otros procedimientos endovasculares (13,14).…”
Section: Introductionunclassified